DATA PROTECTION MECHANISMS IN PEER-TO-PEER NETWORKS - LUZHETSKYY, VOLODYMYR; SAVYTSKA, LIUDMYLA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The article examines the problems of data protection in peer-to-peer networks. Such networks are becoming increasingly popular for communication due to their flexibility, efficiency, and resilience to failures. However, they remain vulnerable to various types of attacks, in particular DoS/DDoS attacks, data falsification, and information interception. The main attention is paid to ensuring the confidentiality, availability, and integrity of data during their transmission and storage, as well as the authentication of nodes to counteract unauthorized access and identity substitution. The analysed approaches in the article are based on modern cryptographic methods, such as symmetric and asymmetric encryption, as well as end-to-end encryption. The use of hash functions allows for data integrity control and detection of their modification. Digital signatures provide authentication of the data source and confirm their immutability. Anonymization and pseudonymization mechanisms are also considered to protect metadata and maintain the confidentiality of communication participants. Availability is ensured by caching, automatic updates after failures, data replication, and decentralized resource management.Particular attention is paid to methods for detecting anomalies in network activity based on the analysis of node behavior and the use of machine learning algorithms and fuzzy logic. The proposed mechanisms for countering attacks include blacklists for blocking suspicious nodes, dynamic change of data transmission routes to protect against man-in-the-middle attacks, and self-isolation methods to minimize the risks of spreading threats. It is proposed to introduce a zero-trust model to increase the security of peer-to-peer networks.
Keywords: peer-to-peer network; encryption; authentication; hash function; data protection; cyber threat; cyber attack; blacklist; digital signature; blockchain; zero trust model